THE POSSIBILITIES OF EVALUATION OF GAME SKILLS AND GAME PERFORMANCE IN FRISBEE ULTIMATE (Fiep Bulletin - online, 2014)
In the study there are presented the possibilities of evaluation of game skills and game performance in frisbee ultimate. The aim of the study was to verify the reliability of the test of a game skill and of game, evaluation methods for physical education and sport. Specifically the reliability of the test of the game skill passing was verified, which had two alternatives – passing at the aim and passing for accuracy to scored areas. Furthermore there was verified the method of evaluation of game performance, based on critical cases. The research was carried out on grammar school students and players of frisbee ultimate. The reliability of the test of a game skill was verified in individual years of study of the grammar school and for boys and girls. The reliability of the method of the evaluation of game performance was verified in the group of frisbee ultimate players. Game performance was evaluated by three experts. The reliability of the test of the game skill was statistically evaluated by ICC and Kendall`s coefficient of concordance were used for statistical analysis. The level of statistical significance was set at 5%. The results showed sufficient reliability of the test of the game skill passing. In case of an alternative passing at the aim the reliability values were from 0,67 to 0,94. In the alternative of passing for accuracy to scored areas the values were from 0,72 to 0,98. Evaluation of game performance was divided into three parts: positive critical cases (W=1), negative critical cases (W=0,8 - p
Keywords: sport games; frisbee ultimate; game skills; game performance; testing; scaling; reliability